Pengaruh Pupuk Organik Dan Anorganik Terhadap Pertumbuhan Pada Tanaman - Trisna Sari Mendrofa (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This research investigates the influence of organic and inorganic fertilizers on plant development and productivity. Organic fertilizers enhance soil fertility and stimulate biological activity through the use of natural inputs such as compost and manure. Meanwhile, inorganic fertilizers supply nutrients more rapidly and in precise amounts but may have long-term impacts on soil quality. A randomized complete block design was used to test different fertilization treatments. The findings reveal that a balanced application of both fertilizer types yields superior plant performance and harvest results. This supports the need for sustainable nutrient management practices to improve crop outcomes without compromising soil integrity.